Review and assessment of the quality of applications related to diet man-agement using the Mobile App Rating Scale (MARS) - Lewartowski, Kamil; Miłosz, Marek (Journal of Computer Sciences Institute, 2025)
This article presents an evaluation of mobile applications for diet management using the Mobile App Rating Scale. The study identifies key factors influencing app quality, analyzes user engagement and satisfaction, and explores the impact of these apps on dietary behavior change. Four popular applications: Fitatu, Dine4Fit, FIT-WORLD, and Foodvisor - were assessed based on their features, functionality, aesthetics, and information quality. The results highlight that Foodvisor stands out with the highest overall ratings, particularly in user engagement and aesthetics. Conversely, Fit-World scored the lowest in several categories, emphasizing the need for improvement in functionality and user-specific features. These findings provide insights into enhancing app design to improve user experience and effectiveness in diet management.